An Analysis of the Islamic Capital Market as an Alternative Income Source for Gen Z Students: A Case Study from Faculty of Islamic Economics and Business - Amirullah, Sir Haykal Alam; Nabila, Adzkia; Aizzah, Dwi Izky; Putra Habibi, M Dhuha Agfa Davi (International Journal of Islamic Thought and Humanities, 2025)
This study is motivated by the need for students to obtain flexible alternative income without disrupting their tight academic schedules. This research aims to analyse the potential of the Islamic capital market as an income source for Gen Z students, with a case study at the Faculty of Islamic Economics and Business (FEBI) UINSA. Using a descriptive qualitative method, data were collected through in-depth interviews with three student investors with diverse backgrounds, triggers, and initial capital. The results indicate a direct correlation between preparatory research and profitability, whereas emotion-based investing (FOMO) leads to underperformance. The study's key finding is that initial capital size is not the primary determinant of success; the participant with the lowest capital achieved the highest nominal profit through strong fundamental and technical analysis. The study concludes that the Islamic capital market has significant potential as an alternative income source for students, provided it is supported by adequate literacy and methodology, and recommends that educational institutions strengthen capital market education to mitigate speculative risks.